DEBUNKING AIDS MYTHS - Lindegger, Graham (PINS-Psychology in Society, 2025)
Cullinan, K & Thom, A (eds) (2009) The virus, vitamins and vegetables: The South African HIV/AIDS mystery. Johannesburg: Jacana Media. ISBN 978-1-77009-691-2 pbk. Pages xvi + 211. I read this remarkable book in the time between the soccer World Cup in July 2010 and the public sector strike in August 2010. These two events seemed to represent a synopsis of South Africa at present, capable on the one hand of world class delivery and excellence, and on the other hand complete lack of care and interest in the wellbeing of children and the sick. This also describes the history of the HIV/AIDS pandemic in South Africa. On the one hand, South African scientists have made an extraordinary contribution to HIV/AIDS. The remarkable microbicide breakthrough was announced at the International AIDS Conference recently; the first clinical trials of a South African HIV vaccine are about to start; and last year a group of South Africans was invited to Canada to help establish the Canadian HIV Vaccine Initiative, because of the great success of the South African equivalent. These events point to the extraordinary role of South Africans in the pioneering work on HIV/AIDS. But on the other hand, South Africa has been the polecat of the world because of the government’s attitude to and stand on the treatment of HIV/AIDS. Sadly this book is about the shamefulness of South Africa in the HIV pandemic, rather than its successes. But just like apartheid atrocities, this is a story which must be told and the abuses exposed. This book does a remarkable job of the latter. The introductory chapter describes the book as giving an account of the “madness, sheer weirdness and despair of a decade with Mbeki and Tshabalala-Msimang” (px). It does this impressively.